Roux-en-Y Gastric Bypass 10 Year Follow-up: The Found Population - Mehaffey, J. Hunter (Surg Obes Relat Dis, 2015)
BACKGROUND: The long-term durability of Roux-en-Y Gastric Bypass (RYGB) remains ill defined in the American population secondary to poor follow-up after bariatric surgery. OBJECTIVE(S): This study evaluated the lost population to better define the long-term durability of RYGB for weight loss and comorbidity amelioration. METHODS: All patients (n=1,087) undergoing RYGB at a single institution between1985-2004 were evaluated. Univariate differences in preoperative comorbidities, post-operative complications, annual weight-loss and 10-year comorbidities were analyzed to compare outcomes between patients with routine follow-up and those without. Using Electronic Medical Record (EMR) review for all encounters at our academic medical center and telephone survey we obtained data for patients lost to follow-up. RESULTS: Among 1,087 RYGB patients, 151 (14%) had consistent 10-year follow up in our prospectively collected database with yearly clinic visits beyond 2 years postoperatively. EMR review and telephone survey data was collected on an additional 500 (46%) patients resulting in 60% of patients having 10-year follow-up after RYGB. There was no statistical difference in any preoperative or postoperative variables between the two groups. We demonstrated no difference in comorbidity prevalence preoperatively or at 10 years between groups. Examination of percent excess BMI lost at yearly intervals revealed no difference between the groups at each interval to 10 years (p= 0.36). CONCLUSIONS: We demonstrated there is no difference in 10-year outcomes including weight loss and comorbidity reduction between patients with routine clinic visits and those lost to follow-up. These 10-year data address the gap in knowledge resulting from poor long-term follow-up after bariatric surgery.